2012
DOI: 10.1200/jco.2012.30.15_suppl.e14521
|View full text |Cite
|
Sign up to set email alerts
|

F-box and WD repeat domain-containing 7 (FBXW7) mRNA and outcome in biliary tract cancer.

Abstract: e14521 Background: Thestandard treatment for biliary tract cancer is gemcitabine plus platinum, but median progression-free survival (PFS) is only 5-8 months (m) (Valle et al, NEJM 2010). Gene expression or somatic mutations may influence the clinical phenotype, which will affect decisions on individualized treatment. Methods: We retrospectively analyzed tissue blocks from 54 advanced or metastatic cholangiocarcinoma, gallbladder or ampulllary cancer patients (p) treated with single-agent gemcitabine or gemci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…El Intergrupo Latinoamericano de Oncología Gastrointestinal (ILOGI) analizó el estado transcripcional de genes que pueden ser usados como factores con valor predictivo y pronóstico en 54 muestras de pacientes con cáncer de vías biliares [incluidos CVB, colangiocarcinoma (CC) y cáncer de la ampolla de Vater]. Entre estos, los niveles de ARN mensajero (ARNm) de FBXW7, un gen que codifica para una ubiquitina ligasa que interacciona con oncoproteínas, se correlacionaron con la supervivencia libre de progresión y SG en 19 pacientes 47 . La mediana de SLP fue 4.9, 7.6 y 26.9 meses para los tumores con niveles de expresión de FBXW7 en los tercilos bajo, medio y alto, respectivamente; la mediana de SG fue 6.2, 8.8 y no alcanzada, respectivamente.…”
Section: Molecularesunclassified
“…El Intergrupo Latinoamericano de Oncología Gastrointestinal (ILOGI) analizó el estado transcripcional de genes que pueden ser usados como factores con valor predictivo y pronóstico en 54 muestras de pacientes con cáncer de vías biliares [incluidos CVB, colangiocarcinoma (CC) y cáncer de la ampolla de Vater]. Entre estos, los niveles de ARN mensajero (ARNm) de FBXW7, un gen que codifica para una ubiquitina ligasa que interacciona con oncoproteínas, se correlacionaron con la supervivencia libre de progresión y SG en 19 pacientes 47 . La mediana de SLP fue 4.9, 7.6 y 26.9 meses para los tumores con niveles de expresión de FBXW7 en los tercilos bajo, medio y alto, respectivamente; la mediana de SG fue 6.2, 8.8 y no alcanzada, respectivamente.…”
Section: Molecularesunclassified
“…The Gastrointestinal Oncology Latin-American Intergroup (ILOGI) analyzed the transcriptional level of different genes as predictive or prognostic factors in 54 BTC samples (including GBC, CC and ampullary cancer). Among others the mRNA level of FBXW7 a gene that encodes an ubiquitin ligase that interacts with oncoproteins, correlated with progression free survival (PFS) and overall survival (OS) in 19 patients (47). Median PFS was 4.9, 7.6 and 26.9 months for tumors in the lowest, middle and upper tercile of expression level.…”
Section: Molecular Pathology Of Gbcmentioning
confidence: 99%
“…Dr. Parada, and outstanding geneticist in Salta, was invited to write the second part of the article. Dr. Parada, who has been working in basic research on hepatobiliary cancer for many years, reviewed the current literature and found that many risk factors and molecular abnormalities of GC have been described by investigators from South America [4][5][6][7][8][9][10]. The third part, which I analysed, was related to the clinical experience.…”
mentioning
confidence: 99%